Hospitalizations among people with Down syndrome: A nationwide population‐based study in Denmark123. Issue 4 (12th February 2013) - Zhu, Jin Liang; Hasle, Henrik; Correa, Adolfo; Schendel, Diana; Friedman, J.M.; Olsen, Jørn; Rasmussen, Sonja A.
Abstract Most persons with Down syndrome (DS) now survive to adulthood, but their health care needs beyond childhood are not well described. We followed a national cohort of 3, 212 persons with DS and a reference cohort of persons without DS through the Danish National Hospital Register from January 1, 1977, to May 31, 2008. Poisson regression was used to calculate rate ratios for numbers of overnight hospital admissions and hospital days. During the study period, persons with DS had more than twice the rate of hospital admissions and nearly three times as many bed‐days as the population as a whole. Malformations, diseases of the respiratory system, and diseases of the nervous system or sensory organs were the principal indications for hospital admissions. The higher rate ratios for hospital admissions were seen especially among persons less than 20 years of age. Hospitalizations for neoplasms or for diseases of the musculoskeletal system or connective tissue were much less frequent among adults with DS. As survival among persons with DS continues to improve, these findings are likely to be useful for health care planning, although the potential utility may be different for different health care systems. © 2013 Wiley Periodicals, Inc.